Potent effects of alkaloid-rich extract from Huperzia selago against sodium nitroprusside-evoked PC12 cells damage via attenuation of oxidative stress and apoptosis - Lenkiewicz, Anna Magdalena; Czapski, Grzegorz Arkadiusz; Jęsko, Henryk; Wilkaniec, Anna; Szypuła, Wojciech; Pietrosiuk, Agnieszka; Uszyńska, Aneta Marta; Adamczyk, Agata (Folia Neuropathologica, 2016)
Imbalance between production and scavenging of free radicals and other reactive oxygen species (ROS) is a component of many diseases, but it is especially important in aging-related diseases of the central nervous system. Oxidative stress-induced neuronal dysfunction plays an important role in the pathomechanism of neurodegenerative disorders, including Alzheimer’s and Parkinson’s disease. Experimental data showed that free radical scavengers may protect the brain against oxidative modifications. The need for efficient and safe antioxidants with therapeutic potential stimulated the rise of interest in the medicinal plant products, which are a rich source of phytochemicals possessing biological activity. In our studies we focused on alkaloid fractions (AFs) isolated from club moss, Huperzia selago and Diphasiastrum complanatum, due to their beneficial activity and exclusive chemical structure. Our previous study demonstrated that selected alkaloids from Huperzia selago effectively protect macromolecules from oxidative damage. Therefore, in the present study we investigated the effects and mechanisms of action of AFs isolated from Huperzia selago and Diphasiastrum complanatum against sodium nitroprusside (SNP)-induced oxidative injury in PC12 cells. The results demonstrated that the selected AFs via reduction of nitric oxide (NO) liberation protected cells against oxidative stress, DNA and mitochondrial damage, as well as apoptosis caused by SNP. Selected AF notably decreased SNP-evoked mitochondrial polymerase γ (Polg) up-regulation. Furthermore, AF which contains Lycopodine, Serratidine, Lycoposerramine-G and (probably) Cermizine B completely inhibited the SNP-induced expression of interferon-γ (Ifng) and cyclooxygenase 2 (Ptgs2) as well as significantly down-regulated the expression of 12/15-lipoxygenase (Alox12) and tended to decrease the mRNA level of interleukin-6 gene (Il6). In conclusion, these results suggest that the AFs from Huperzia selago effectively protect PC12 cells against SNP-induced oxidative damage by adjusting the level of reactive nitrogen species, suppression of apoptosis and down-regulation of proinflammatory genes. The compounds present in these AFs could be potential candidates to develop successful drugs preventing oxidative damage and apoptosis in age-related neurodegenerative disorders.